2011
DOI: 10.3146/ps10-19.1
|View full text |Cite
|
Sign up to set email alerts
|

Row Pattern and Seeding Rate Effects on Agronomic, Disease, and Economic Factors in Large-Seeded Runner Peanut

Abstract: Recent peanut cultivar releases are trending to a larger seed size, but have great resistance to tomato spotted wilt virus (TSWV). Larger-seeded cultivars cost more to plant than smaller at an equivalent population. Reduced seeding rates could save growers on seed costs and impede the spread of southern stem rot, but can reduce plant stands which can lower yields and increase TSWV incidence. Therefore, the objectives of this experiment were to compare seven peanut cultivars (Georgia Green, Georgia-06G, AT 3085… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…Although data is limited on plant stand effects on pod yield in peanut seeded in twin rows, Lanier et al (2004) reported no differences in yield between stands of 4, 8, and 12 plants/m using four Virginia-type peanut cultivars. While overall plant stands tested were higher, Tubbs et al (2011) reported a similar effect in twin rows, with a plant stand of 16.3 plants/m producing higher yields than stands of 15.7 and 13.6 plants/m across seven Runner-type cultivars.Peanut grade was also affected by plant stand. Similar to pod yield, the highest grade value was observed at 12.3 plants/m.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Although data is limited on plant stand effects on pod yield in peanut seeded in twin rows, Lanier et al (2004) reported no differences in yield between stands of 4, 8, and 12 plants/m using four Virginia-type peanut cultivars. While overall plant stands tested were higher, Tubbs et al (2011) reported a similar effect in twin rows, with a plant stand of 16.3 plants/m producing higher yields than stands of 15.7 and 13.6 plants/m across seven Runner-type cultivars.Peanut grade was also affected by plant stand. Similar to pod yield, the highest grade value was observed at 12.3 plants/m.…”
mentioning
confidence: 83%
“…Tubbs et al (2011) reported reduced pod yield in twin rows at seeding rates of 17 and 20 seeds/m when compared to a seeding rate of 23 seeds/m. While not implicitly studied, the 17 and 20 seeds/m rates resulted in plant stands of 13.6 and 15.7 plants/m, respectively, while the 23 seeds/m seeding rate corresponded to a final plant stand of 16.3 plants/m.…”
mentioning
confidence: 99%
“…In this experiment TSW incidence was relatively low even though yield was higher in twin rows compared with single rows. Planting peanut in twin rows is more expensive than planting in single rows because the amount of seed, in-furrow insecticide, and inoculant input costs are increased (Tubbs et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In 4 of 6 trials, planting peanut in twin rows increased yield by 330 to 550 kg/ha over single rows regardless of cultivar (Table 3). Yield response to planting pattern can be inconsistent (Baldwin et al, 2001;Buchanan and Hauser, 1980;Hurt et al, 2003;Jordan et al, 2001;Tubbs et al, 2011). Increasing the seeding rate or planting peanut in twin row patterns is a key component of risk advisories for TSW management in peanut (Brandenburg, 2014;Hurt et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Tomato spotted wilt (tomato spotted wilt tospovirus) in peanut became epidemic in the southeastern U. S. region during the early 1990's and seeding rates to produce a final stand of .13 plants/m of row were recommended to reduce losses due to the disease (Culbreath et al 2003(Culbreath et al , 2013Tillman et al 2006;Tubbs et al 2011). The premise was that dense peanut growth was less attractive to thrips vectors and compensated for early-season stand losses due to the disease.…”
mentioning
confidence: 99%